2018
DOI: 10.1177/1055665618802151
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Cephalometric Study of Nasoalveolar Molding– and Non-Nasoalveolar Molding–Treated Bilateral Cleft Patients at Early Mixed Dentition Period

Abstract: Objective: To evaluate and compare early maxillary growth in 2 groups of patients with repaired bilateral cleft lip and palate (BCLP) who had and had not received nasoalveolar molding (NAM) therapy in infancy. Hypothesis: Nasoalveolar molding does not have any effect on maxillomandibular growth at the early mixed dentition period. Design: Retrospective study. Patients: The study group consisted of forty-two 7-year-old patients with BCLP—20 in the NAM group and 22 in the no-NAM group. The control group co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In another study, cephalometric evaluation of skeletal and dental relationships in the early mixed dentition phase revealed no statistically significant difference between the NAM and non-NAM groups. 29 In the present study, the effects of NAM therapy on arch dimensions were examined in patients with BCLP in primary dentition, and no significant difference was observed between the NAM and non-NAM groups.…”
Section: Discussionmentioning
confidence: 75%
“…In another study, cephalometric evaluation of skeletal and dental relationships in the early mixed dentition phase revealed no statistically significant difference between the NAM and non-NAM groups. 29 In the present study, the effects of NAM therapy on arch dimensions were examined in patients with BCLP in primary dentition, and no significant difference was observed between the NAM and non-NAM groups.…”
Section: Discussionmentioning
confidence: 75%
“…A comparison of surgery alone to a combination of NAM and primary rhinoplasty with overcorrection showed that patients receiving both had optimal results, closest to the nasal form of unaffected infants at 3 years of age (Chang et al, 2014). With respect to future growth, evidence shows that in evaluation of 7-year-old patients with BCLP, NAM did not have an effect of maxillomandibular growth compared to patients of the same age who underwent primary surgeries without presurgical NAM (Nayak et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a presurgical therapy, it improves predicted and actual postsurgical outcomes [36] . The evidence suggests an overall reduced total cost of care [37] due to decreased rates of secondary procedures [38,39] .…”
Section: Limitationsmentioning
confidence: 99%